Improving Reading Comprehension Skills Through Cooperative Learning Stad in Grade IV Students of SDN 08 Surau Gadang - Gevina Miftah Hulzannah Hasibuan; Azkiya, Hidayati; Morelent, Yetty; Isnanda, Romi (The Future of Education Journal, 2025)
This research is motivated by (1) Teachers still use the lecture method, so that students look bored, (2) Lack of students' ability to participate, (3) Lack of students' ability to cooperate in learning. The purpose of this research is to improve the reading comprehension skills of grade IV students of SDN 08 Surau Gadang Nanggalo Padang. This type of research is Classroom Action Research (PTK) which includes 4 stages, namely planning, implementation, observation, and reflection with a total of 25 students. The research instruments used are observation sheets and learning outcome tests. Based on the results of research conducted in the first cycle on the teacher's activity sheet, 74,21% increased in the second cycle to 87,5%. Meanwhile, the student activity sheet in the first cycle was 62.49%, an increase in the second cycle of 83.33%. The results of students' reading ability in the first cycle obtained an average of 63.98, while in the second cycle the average increased to 83.97. Based on the results of the study, it can be concluded that using the STAD (Student Team Achievement Division) type cooperative learning model in Indonesian learning can improve the reading comprehension skills of grade IV students of SD IT Nurul Ikhlas Padang. Suggestions for the use of the STAD (Student Team Achievement Division) type cooperative learning model in Indonesian learning help improve students' reading comprehension skills in Indonesian learning as information and comparison materials for the implementation of similar and relevant research.